Model Rantai Pasok Pada Sistem Produksi Menggunakan Petri Net dan Aljabar Max Plus - ahmad afif; Dian Mustofani (Mathematics Department of Mathematics and Natural Sciences Unisda Lamongan, 2019)
Abstract. Supply chain production system is a process of coordination and integration of activities ranging from the procurement of goods and services, transforming raw materials into semi-finished goods and finished goods, to distribute to the consumers in an efficient manner. Supply chain analysis is used to regulate the supply of the production system so as not to overload so that it can reduce the costs of the entire production system which includes the costs of processing, transportation and distribution of raw materials, semi-finished goods and finished goods. Petrinet can describe the supply chain model as a dynamic production systems with discrete events with max plus algebra approach to help calculate the length of time in the distribution and production in the supply chain. Keywords: supply chain, production system, petri net, max plus algebra Abstrak. Rantai pasok pada sistem produksi merupakan proses koordinasi dan integrasi kegiatan mulai dari pengadaan barang dan jasa, mengubah bahan baku menjadi barang setengah jadi dan barang jadi, hingga mendistribusikan kepada konsumen dengan cara efisien. Analisis rantai pasok dipakai untuk mengatur pasokan dari sistem produksi supaya tidak terjadi overload sehingga dapat mengurangi biaya dari keseluruhan sistem produksi yang meliputi biaya pengolahan, transportasi dan distribusi bahan baku, barang setengah jadi dan barang jadi. Petrinet dapat menggambarkan model rantai pasok sebagai sistem produksi yang dinamis dengan kejadian diskrit dengan pendekatan aljabar max plus untuk membantu menghitung lamanya waktu dalam pendistribusian dan produksi dalam rantai pasok. Kata kunci : rantai pasok, sistem produksi, petri net, aljabar max plus